2006
DOI: 10.1016/j.labeco.2005.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The latin model of welfare: Do ‘insertion contracts’ reduce long-term dependence?

Abstract: This paper aims to present an assessment of the welfare policies implemented in most South European countries. Welfare programs in these countries try to combine a basic level of economic protection and measures favoring life and labor skills ('insertion benefits') of low-income households. We focus on a specific program set up with the twofold strategy of cash and 'insertion benefits' (Madrid's IMI) and, more precisely, on the so-called 'insertion projects', consisting in a gradual mix of job search assistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
0
8
0
5
Order By: Relevance
“…The results show that this can be explained by personal and social conditions acting as barriers to labour market integration (Dan zinger et al, 2000;Ayala andRodriguez, 2006 and. The mediating role played by individual factors in the effectiveness of public intervention is an interesting issue that can be analysed by looking at the links between the socio-demographic and personal problems of social assistance recipients and their chances of fi nding employment.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The results show that this can be explained by personal and social conditions acting as barriers to labour market integration (Dan zinger et al, 2000;Ayala andRodriguez, 2006 and. The mediating role played by individual factors in the effectiveness of public intervention is an interesting issue that can be analysed by looking at the links between the socio-demographic and personal problems of social assistance recipients and their chances of fi nding employment.…”
Section: Introductionmentioning
confidence: 94%
“…Most of the studies provide evidence on the effects of socio-demographic characteristics of households, but it is less common to provide information on the personal and social problems of welfare benefi ciaries (Ayala andRodriguez, 2006, 2007). It is generally agreed that the chances of entering the labour market increase with education levels or work experience, and that certain characteristics of households, such as being a single parent with dependent children, tend to make the transition to employment more diffi cult.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…La evaluación de las políticas activas de empleo, y concretamente de los programas de formación, tiene un largo recorrido en Estados Unidos y Europa, pero en España no ha sido hasta la década de los 90 que se ha experimentado un aumento de la cultura evaluadora, ejemplo de ello son las investigaciones de Alujas Ruíz y López Tamayo (2006), Ayala y Rodríguez (2006, Buendía Eisman, Expósito López y Sán-chez Martínez (2012), de Miguel, San Fabián La evaluación de las políticas activas de empleo viene justificada por la necesidad de determinar la efectividad y la eficacia. La efectividad en el logro de los objetivos propuestos y la eficacia en términos de relación entre el logro de objetivos y recursos invertidos para alcanzarlos.…”
Section: Razones Y Finalidades De La Evaluaciónunclassified
“…This weak conditionality of benefit receipt to compliance with insertion contracts is reinforced by the fact that the administration in charge of benefit payment differs from the one in charge of the insertion contracts. So, although such 'insertion contracts' have been found to reduce welfare dependency in the Spanish case (Ayala and Rodríguez, 2006), doubt can be cast on the actual efficiency of such non pecuniary incentives in the French case. Although Zoyem (2001) has found that such contracts had a positive effect on transitions from welfare to work, his study does not correct for the endogeneity of contracts, thereby over-estimating their effects.…”
mentioning
confidence: 99%